Birth as a neuro-psycho-social event: An integrative model of maternal experiences and their relation to neurohormonal events during childbirth - Olza, Ibone; Uvnäs-Moberg, Kerstin; Ekström-Bergström, Anette; Leahy-Warren, Patricia; Karlsdóttir, Sigfrídur Inga; Nieuwenhuijze, Marianne J.; Villarmea, Stella; Hadjigeorgiou, Eleni; Kaźmierczak, Maria; Spyridou, Andria; Buckley, Sarah J. (My University, 2020)
Background Psychological aspects of labor and birth have received little attention within maternity care service planning or clinical practice. The aim of this paper is to propose a model demonstrating how neurohormonal processes, in particular oxytocinergic mechanisms, not only control the physiological aspects of labor and birth, but also contribute to the subjective psychological experiences of birth. In addition, sensory information from the uterus as well as the external environment might influence these neurohormonal processes thereby influencing the progress of labor and the experience of birth. Methodology In this new model of childbirth, we integrated the findings from two previous systematic reviews, one on maternal plasma levels of oxytocin during physiological childbirth and one meta-synthesis of women's subjective experiences of physiological childbirth. Findings The neurobiological processes induced by the release of endogenous oxytocin during birth influence maternal behaviour and feelings in connection with birth in order to facilitate birth. The psychological experiences during birth may promote an optimal transition to motherhood. The spontaneous altered state of consciousness, that some women experience, may well be a hallmark of physiological childbirth in humans. The data also highlights the crucial role of one-to-one support during labor and birth. The physiological importance of social support to reduce labor stress and pain necessitates a reconsideration of many aspects of modern maternity care. Conclusion By listening to women’s experiences and by observing women during childbirth, factors that contribute to an optimized process of labor, such as the mothers’ wellbeing and feelings of safety, may be identified. These observations support the integrative role of endogenous oxytocin in coordinating the neuroendocrine, psychological and physiological aspects of labor and birth, including oxytocin mediated. decrease of pain, fear and stress, support the need for midwifery one-to-one support in labour as well as the need for maternity care that optimizes the function of these neuroendocrine processes even when birth interventions are used. Women and their partners would benefit from understanding the crucial role that endogenous oxytocin plays in the psychological and neuroendocrinological process of labor.
Keywords: Corticotropin releasing factor; Neurohormone; Oxytocin receptor; Oxytocin